2016
DOI: 10.1002/2016gl070342
|View full text |Cite
|
Sign up to set email alerts
|

Deepwater circulation variation in the South China Sea since the Last Glacial Maximum

Abstract: Deepwater circulation plays a central role in global climate. Compared with the Atlantic, the Pacific deepwater circulation's history remains unclear. The Luzon overflow, a branch of the North Pacific deep water, determines the ventilation rate of the South China Sea (SCS) basin. Sedimentary magnetic properties in the SCS reflect millennial‐scale fluctuations in deep current intensity and orientation. The data suggest a slightly stronger current at the Last Glacial Maximum compared to the Holocene. But, the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 64 publications
4
27
0
Order By: Relevance
“…On the other hand, increased intermediate-water temperature in the subtropical Pacific recorded in core GH08-2004 (1166 m water depth) (Kubota et al, 2015) and young deep water observed in the northern South China Sea during HS1 (Wan and Jian, 2014) along the downstream region of the NPIW are also related to an intensified NPIW formation. Furthermore, the pathway of GNPIW from numerical model simulations (Zheng et al, 2016) was similar to modern observations (You, 2003). Thus, all of this evidence implies a persistent cause-andeffect relation between GNPIW ventilation, the intermediate and deep water oxygen concentration in the OT, and sediment redox state during HS1.…”
Section: Effects Of Gnpiw On Sedimentary Oxygenationsupporting
confidence: 71%
“…On the other hand, increased intermediate-water temperature in the subtropical Pacific recorded in core GH08-2004 (1166 m water depth) (Kubota et al, 2015) and young deep water observed in the northern South China Sea during HS1 (Wan and Jian, 2014) along the downstream region of the NPIW are also related to an intensified NPIW formation. Furthermore, the pathway of GNPIW from numerical model simulations (Zheng et al, 2016) was similar to modern observations (You, 2003). Thus, all of this evidence implies a persistent cause-andeffect relation between GNPIW ventilation, the intermediate and deep water oxygen concentration in the OT, and sediment redox state during HS1.…”
Section: Effects Of Gnpiw On Sedimentary Oxygenationsupporting
confidence: 71%
“…Similarities in physical and chemical properties of deep waters between the SCS and the Pacific at 2000 water depth (Chang et al, 2010;Wang et al, 2011;Wyrtki, 1961) reveal that the SCS deep water comes from the deep water of the open western Pacific, which is primarily originated from the Southern Ocean nowadays (Kawabe & Fujio, 2010). Proxies of deep water ventilation age (i.e., the difference between coexisted benthic and planktic 14 C age) (Wan & Jian, 2014), foraminiferal neodymium isotope (ENd) (Wu et al, 2015) and sedimentary magnetic properties (Zheng et al, 2016) in the SCS have been also used to reconstruct the history of the Pacific intermediate/deep circulation since the last glacial period. Therefore, the SCS offers a unique opportunity for understanding the deep circulation in the low-latitude western Pacific during the glacial cycle (Jian & Wang, 1997;Qu et al, 2006;Tian et al, 2006;Wan & Jian, 2014;Wu et al, 2015;Zheng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…L. Zhao et al, 2015, and references therein; Figure 1b). Previous studies of the SCS sediments have demonstrated that contour currents is strengthened during Heinrich stadials deduced from the striking increase of both magnetic susceptibility and mean size of sortable silt Zheng et al, 2016), coinciding with a period of the weakened East Asian summer monsoon (Sun et al, 2012;Y. J. Wang et al, 2001;Wen et al, 2016).…”
Section: Paleoceanography and Paleoclimatologymentioning
confidence: 92%
“…As an outcome of the North Pacific Deep Water intrusion to the SCS through Luzon Strait, the contour currents characterized by a tunnel-like vertical structure flow along the continental slope at water depth of around 1,650-2,000 m inferred from modern in situ observations (W. Zhao et al, 2014;Y. Previous studies of the SCS sediments have demonstrated that contour currents is strengthened during Heinrich stadials deduced from the striking increase of both magnetic susceptibility and mean size of sortable silt Zheng et al, 2016), coinciding with a period of the weakened East Asian summer monsoon (Sun et al, 2012;Y. Previous studies of the SCS sediments have demonstrated that contour currents is strengthened during Heinrich stadials deduced from the striking increase of both magnetic susceptibility and mean size of sortable silt Zheng et al, 2016), coinciding with a period of the weakened East Asian summer monsoon (Sun et al, 2012;Y.…”
Section: Paleoceanography and Paleoclimatologymentioning
confidence: 95%